PENGARUH SERVANT LEADERSHIP DAN BUDAYA ORGANISASI SEKOLAH TERHADAP KINERJA GURU PADA SEKOLAH MENENGAH ATAS NEGERI DI KOTA PADANG - Fitrah Santosa; Adrianto Adrianto; Syamsir Syamsir; Afriva Khaidir (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2019)
The objectives of this study were: 1) to determine the effect of servant leadership on teacher performance in-state senior high schools in the city of Padang. 2) to determine the effect of school organizational culture on teacher performance in-state senior high schools in the city of Padang. This study used an associative quantitative method, the population of this study were all-state senior high school teachers in the city of Padang, with a sample of 292 teachers. Analysis of the data used in this study is a regression analysis technique, in addition, the researchers also used descriptive analysis to obtain a descriptive measurement from each research variables. The results of this study are: 1) servant leadership has a positive and significant effect on teacher performance in State Senior High Schools in the City of Padang. 2) school organizational culture has a positive and significant effect on teacher performance in State Senior High Schools in the city of Padang.